“Forgetting Afghan War? No, It Is Impossible”: The Evolution of the Soviet-Afghan War (1979-1989) In Perception of the Russian Collective Consciousness and In the Russian Political Discourse .......... 379 (Czas w kulturze rosyjskiej, 2019)
“FORGETTING AFGHAN WAR? NO, IT IS IMPOSSIBLE”. THE EVOLUTION OF THE SOVIET-AFGHAN WAR (1979-1989) IN PERCEPTION OF THE RUSSIAN COLLECTIVE CONSCIOUSNESS AND IN THE RUSSIAN POLITICAL DISCOURSE The article discusses changes in the public consciousness of the Russians during recent thirty years, relating to the ways the Soviet-Afghan war (1979-1989) was perceived by the Soviet and afterwards by the Russian society. The article also analyses changes in the presentation of the mentioned armed conflict in the official Soviet and Russian mass media. Another important issue mentioned in the text is the phenomenon of the memory revision process that has obviously increased its impact in the last decade, and is manifested, in particular, in stopping forgetting the Soviet-Afghan war and the rehabilitation of its participants, which is more and more visible. The perception of the Soviet-Afghan war in the post-Soviet-Russian society over the past thirty years has evolved markedly: from the gradual oblivion and condemnation by different segments of society to the acquisition of a solid place in the Russian social memory. Particular attention in this article was given to the idea of time characteristic for the studied culture at the turn of the 21st century: the political category of time, political and social changes connected with time were analysed. It is worth emphasizing that time in processes perceived and created by people (e.g. war) is not objective. Time begins to acquire its value only when someone evaluates it.